Implementasi Dakwah Bil-Lisan dalam Meningkatkan Pemahaman Agama Masyarakat - Fachrul Rozy Sinambela; Mutiawati (Dakwah Institut PTIQ Jakarta, 2022)
The purpose of this study is to ascertain how the implementacion of Bil-Lisan da'wah is boosting people's religious comprehension. This kind of research is called qualitative research, and it collects data from the field, analyzes it using data, and then shapes that data into hypotheses, phrases, or sentences. In this study, a descriptive method is employed in an effort to characterize and explain things in light of the relevant field facts. According to the study's findings, the oral da'wah method, also known as bil-lisan da'wah, is the most often employed and one of the techniques used to disseminate Islamic da'wah. Implementing bil-lisan da'wah to the general populace.